2021
DOI: 10.1002/pssb.202100230
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Diffusion from MgO Substrates in Sol–Gel‐Derived NiO Epitaxial Films: Effects of Heat Treatment Temperature and Li Doping

Abstract: The effects of heat treatment temperature and Li doping on the structural properties of sol–gel‐derived NiO epitaxial films on MgO (100) substrates are investigated. X‐ray diffraction measurements indicate that the out‐of‐plane lattice parameters of undoped NiO films increase as the heat treatment temperature increases. This increase is particularly significant in films treated above 900 °C, in which out‐of‐plane and in‐plane lattice parameters are larger than the expected values for bulk NiO. This result cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Meanwhile, Kokubun et al reported an increase in the lattice parameters at high heat treatment temperatures caused by Mg diffusion from the MgO substrate to NiO epilayer during the heat treatment in the solgel process. 37) Therefore, it is assumed that there could be Mg diffusion from the MgO substrate near the interface in our experiment. One of the reasons for this irregular interface is the roughness of the MgO substrate before deposition of NiO at 500 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Kokubun et al reported an increase in the lattice parameters at high heat treatment temperatures caused by Mg diffusion from the MgO substrate to NiO epilayer during the heat treatment in the solgel process. 37) Therefore, it is assumed that there could be Mg diffusion from the MgO substrate near the interface in our experiment. One of the reasons for this irregular interface is the roughness of the MgO substrate before deposition of NiO at 500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Epitaxial NiO thin films are grown using oxidation of Ni, 28,29) pulsed laser deposition, 5,6,17,18,21,30,31) electron beam evaporation, 32) molecular beam epitaxy, 33) atomic layer deposition, 34) mist chemical vapor deposition, 35) and sol-gel method. 36,37) Among these, sputtering is the most suitable approach for depositing large-area films with well-controlled compositions economically. However, the epitaxial growth mechanisms of NiO thin films grown by sputtering have not yet been clarified because of the relatively few reported studies.…”
Section: Introductionmentioning
confidence: 99%